Creation and validation of an instrument to identify nursing activities in pediatric wards: information for determining workload - Santos,Nanci Cristiano (2013)
The aim of this study was to develop and validate an instrument for identifying nursing activities performed in a pediatric ward and to provide a basis for defining the workload of these units. The instrument was developed by selecting the activities relevant to pediatric nursing from the Nursing Intervention Classification and then submitting them to a panel of judges for validation. The panel considered the selected activities relevant and representative of pediatric nursing practice. Now that representative activities for the nursing workload have been identified, we envision new studies to verify their usefulness in practice. Determining the amount of time each activity takes to perform will help to develop a system for measuring the workloads of nursing teams in pediatric wards.